The single-cell transcription reveals the aberrant differentiation trajectory of chondrocytes in the intervertebral disc for congenital scoliosis - Wang, Junfeng; Li, Haodong; Fu, Dong; Zheng, Yiming; Qian, Chuang; Li, Lin; Qian, Maoxiang; Wang, Dahui (iScience, 2025)
Cartilage endplate (CEP) in the intervertebral disc (IVD) contributes to vertebral level asymmetrically in congenital scoliosis (CS). However, the cellular compositions of CEP and the subsequent alteration of cellular environment in its neighboring annulus fibrosus and nucleus pulposus remain unknown during the progressive scoliosis. Herein, this study resolved the single-cell landscape of IVD in CS. Chondrocytes in CS demonstrated a different trajectory and were enriched in the cytoskeleton dependent cytokinesis pathways. H19, ECRG4, CCN1, and CCN2 were the specific markers for CS, and DBP may be the critical transcription factor (TF) for CS. Notochord and pericyte were the dominative cell types in the cell-cell communications, among which NCAM and SEMA5 signaling were the unique pathways for CS. Collectively, the aberrant differentiation trajectory of chondrocytes may explain the vertebral dysplasia in CS, and these critical gene markers, TFs, and pathways identified in this study may provide potential therapeutic targets for CS. [Display omitted] •Chondrocytes in CS demonstrated a different differentiation trajectory•H19, ECRG4, CCN1, and CCN2 were the specific markers for CS•DBP may be the critical transcription factor for CS•Intercellular crosstalk identified the key roles of notochord and pericyte in CS Pathophysiology; Transcriptomics